Spatial and Epidemiological Analysis of Tuberculosis Case Distribution and Determinants of Treatment Success in the Working Area of Rowosari Community Health Center (2024-2025) - Amelia Putri Fitriana; Bela Lavinia; Farida Putri Nabila; Mona Prastina; Azka Arani; Supriyono Asfawi (Dian Nuswantoro Semarang, 2026)
Tuberculosis (TB) remains a significant global public health challenge. This study aims to analyze the distribution of TB cases based on the dimensions of time, region, age, gender, and the evaluation of treatment success at Puskesmas Rowosari for the period 2024–2025. The research method uses a quantitative descriptive design with a secondary data study approach from the health center information system. The results show a decrease in case notifications from 134 (2024) to 100 (up to November 2025), with the highest concentration in Meteseh Village (43%) and the productive age group (50%). The treatment success rate reached 89%, but the 7% Lost to Follow-Up rate still poses an elimination challenge. The conclusion emphasizes the need to strengthen area-based surveillance and psychosocial interventions to achieve the TB elimination target for Semarang City by 2028.